(untitled) (Al-Qamar, 2024)
After the beginning of the 20th century and the British domination, such fundamental changes took place at every level of the Indo-Islamic civilization. The majority of the scholars who were fierce in Islam had fallen in front of limited knowledge, communism, capitalism, liberalism and nationalism. In such a difficult time, Islamic thinkers and Sufi saints equipped with Islamic and modern knowledge step ahead and presented themselves for the service of religion. These Islamic thinkers popularized the teachings of Masnavi Manawi through their compilations, articles and various lectures. However, there is historical evidence that these Sufis and their caliphs continued to give priority to the ’Musnawi Maanwi’ in their teachings. In this way, the Islamic ideas and thoughts contained in Masnavi Manawi became popular among the people. As if Masnavi has a big hand in the renaissance of Muslims in the subcontinent, as if Masnavi dominates the entire history of Islamic education in other senses. It has been more or less eight hundred years since Maulana Jalaluddin Rumi (1207-1273) left this world. During this long period, almost every period shows a large number of works on the Masnavi, which gives clear evidence of the popularity and universality of the Masnavi. Masnavi is a book of divine mysteries. Therefore, this valuable work has the status of an inspired book in Iran, Turkey and the Indian subcontinent. In view of the importance and usefulness of Masnavi, many scholars, Sufis and modern thinkers wrote exegesis on it for the convenience of the people. In this article, this exegesis (explanations) will be studied briefly.